Butanol fermentation from microalgae-derived carbohydrates after ionic liquid extraction. (April 2016) - Gao, Kai; Orr, Valerie; Rehmann, Lars
Highlights: Lipid extraction via ionic liquids leave starch rich fraction. Starch rich fraction can be directly fermented to butanol. Acid hydrolysis improves butanol yield. Abstract: Lipid extracted algae (LEA) is an attractive feedstock for alcohol fuel production as it is a non-food crop which is largely composed of readily fermented carbohydrates like starch rather than the more recalcitrant lignocellulosic materials currently under intense development. This study compares the suitability of ionic liquid extracted algae (ILEA) and hexane extracted algae (HEA) for acetone, butanol, and ethanol (ABE) fermentation. The highest butanol titers (8.05 g L −1 ) were achieved with the fermentation of the acid hydrolysates of HEA, however, they required detoxification to support product formation after acid hydrolysis while ILEA did not. Direct ABE fermentation of ILEA and HEA (without detoxification) starches resulted in a butanol titer of 4.99 and 6.63 g L −1, respectively, which significantly simplified the LEA to butanol process. The study demonstrated the compatibility of producing biodiesel and butanol from a single feedstock which may help reduce the feedstock costs of each individual process.